Arrecifes coralinos de Bocas del Toro, Panamá: II. Distribución, estructura y estado de conservación de los arrecifes de las Islas Bastimentos, Solarte, Carenero y Colón - Guzmán, Héctor M. (1998)
The distribution and conservation status of coral reefs along the northern section of the archipelago of Bocas del Toro are evaluated (ca. 120 km), and the structure of 18 reefs around the islands of Bastimentos, Solarte, Carenero and Colón is described. Reef habitats located on the seaward side (exposed) of the islands exhibited the lowest coral cover (8%) and coral diversity, while leeward reefs (protected) showed the highest living coral cover (32%) and diversity. Macroalgae coverage was similar in both habitats but high (50%) if compared with other continental reefs described in the Ensenada Grande of Almirante Bay (4%). A total of 54 coral species was recorded, representing a 35% increase from previous studies for the regíon and 88% of the total species described fOr Panamá. The diversity of reefs, reef organisms and habitats in the archipelago was greater outside the national park of Isla Bastimentos, the only marine protected area in western Panamá. Sorne recommendations are provided for an integrated management of marine-terrestríal natural resources in the region, in particular, a complete change on the existing limits of the protected area and the creation of new reserves.